2019
DOI: 10.5194/essd-11-845-2019
|View full text |Cite
|
Sign up to set email alerts
|

The TRIple-frequency and Polarimetric radar Experiment for improving process observations of winter precipitation

Abstract: Abstract. This paper describes a 2-month dataset of ground-based triple-frequency (X, Ka, and W band) Doppler radar observations during the winter season obtained at the Jülich ObservatorY for Cloud Evolution Core Facility (JOYCE-CF), Germany. All relevant post-processing steps, such as re-gridding and offset and attenuation correction, as well as quality flagging, are described. The dataset contains all necessary information required to recover data at intermediate processing steps for user-specific applicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 51 publications
11
70
1
Order By: Relevance
“…Accurate retrievals of vertical profiles of cloud and precipitation properties from space or from the ground are essential pillars for evaluating and further developing their representation in numerical models (Iguchi and Matsui, 2018). However, a recent study by Duncan and Eriksson (2018) shows, for example, that even essential columnar cloud properties, such as ice water path (IWP), show large biases between different retrieval products, which hampers their applicability to further improve model parameterizations. As mentioned by Duncan and Eriksson (2018) and others, one of the main reasons for the spread between retrieval products but also for differences in models is related to uncertainties in the underlying cloud microphysics.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate retrievals of vertical profiles of cloud and precipitation properties from space or from the ground are essential pillars for evaluating and further developing their representation in numerical models (Iguchi and Matsui, 2018). However, a recent study by Duncan and Eriksson (2018) shows, for example, that even essential columnar cloud properties, such as ice water path (IWP), show large biases between different retrieval products, which hampers their applicability to further improve model parameterizations. As mentioned by Duncan and Eriksson (2018) and others, one of the main reasons for the spread between retrieval products but also for differences in models is related to uncertainties in the underlying cloud microphysics.…”
Section: Introductionmentioning
confidence: 99%
“…snow when PR > 1 mm h −1 , while the reverse is observed for lighter precipitation. Despite the rather good agreement between LDR and ρ hv observations, it appears that LDR systematically reveals lower ML bottom than ρ hv , indicating that LDR can be suitable in discriminating rain and melting snow (Illingworth and Thompson, 2011;Dias Neto et al, 2019). The smaller LDR peak for rimed snow is correlated with the smaller X-band reflectivity enhancement as shown in Fig.…”
Section: Ka-band Ldr and Reflectivitymentioning
confidence: 94%
“…Polarimetric Doppler spectra have only been sporadically used in the past, probably due to the demands regarding storage capacity and required high data quality. At centimeter wavelength, their potential has been shown for microphysical retrievals (Moisseev and Chandrasekar, 2007;Spek et al, 2008;Dufournet and Russchenberg, 2011;Pfitzenmaier et al, 2018) and efficient clutter suppression (Unal, 2009;Moisseev and Chandrasekar, 2009;Alku et al, 2015). The number of installed polarimetric Doppler cloud radars has only recently increased, with only a few studies, so far, exploring their potential for microphysical studies and retrievals (Oue et al, 2015(Oue et al, , 2018Myagkov et al, 2015Myagkov et al, , 2016b.…”
Section: Separating Propagational and Backscattering Components Usingmentioning
confidence: 99%
“…Drop size distributions (DSDs) observed in situ are converted to the radar reflectivity. Time series (Gage et al, 2004;Frech et al, 2017) or distributions (Kollias et al, 2019;Dias Neto et al, 2019) of calculated and observed reflectivities are then compared. Hogan et al (2003) showed a calibration verification method suitable for W-band cloud radars only.…”
Section: Introductionmentioning
confidence: 99%